2003
DOI: 10.1046/j.1365-2672.2003.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress situations induce cyanide-resistant respiration in spoilage yeasts

Abstract: Aims: To investigate the conditions that promote the expression of cyanide-resistant respiration (CRR) in the spoilage yeasts Pichia membranifaciens and Debaryomyces hansenii. Methods and Results: CRR was detected by sensitivity of oxygen consumption to salicylhydroxamic acid. It was absent in both yeasts in the early exponential phase, but was triggered by several stress situations. Starvation under aerobic conditions, decreasing pH or incubation of the culture in a narrow temperature range below the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 27 publications
0
37
2
1
Order By: Relevance
“…Furthermore, the differences occurred at a later stage of growth than those observed in the X-33 PpAOD strain. As the literature links alternative oxidase activity to stress response (Gonzalez-Meler et al, 1999;Kirimura et al, 1996;Ordog et al, 2002;Simons et al, 1999;Vanlerberghe et al, 2002;Veiga et al, 2003b) and therefore to cellular viability we consider increased cell death phenomena as a possible explanation for this discrepancy.…”
Section: Constitutive Expression and Disruption Of The Aod Genementioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the differences occurred at a later stage of growth than those observed in the X-33 PpAOD strain. As the literature links alternative oxidase activity to stress response (Gonzalez-Meler et al, 1999;Kirimura et al, 1996;Ordog et al, 2002;Simons et al, 1999;Vanlerberghe et al, 2002;Veiga et al, 2003b) and therefore to cellular viability we consider increased cell death phenomena as a possible explanation for this discrepancy.…”
Section: Constitutive Expression and Disruption Of The Aod Genementioning
confidence: 88%
“…For example, osmotic stress, chilling (Gonzalez-Meler et al, 1999;Veiga et al, 2003b), wounding, pathogen attack (Simons et al, 1999), and treatment with H 2 O 2 or inhibitors of the main respiratory chain, such as cyanide and antimycin A (Kirimura et al, 1996), have been reported to induce alternative respiration. There is substantial experimental support for the role of alternative oxidases as protecting the cell from reactive oxygen species or providing some metabolic flexibility (Joseph-Horne et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In M. grisea, for example, active oxygen species are thought to be signal mediators to activate transcription of the AOX gene (Yukioka et al 1998), and the superoxide anion ( O 2 •-) is involved in the induction of cyanide-resistant-respiration (CRR) in the yeast H. anomala (Minagawa et al 1992). The presence of H 2 O 2 and menadione induces CRR in Pichia membranifaciens and Debaryomyces hansenii (Veiga et al 2003). Karrafa et al (2001) reported a negative correlation between CRR and intracellular peroxide levels in A. chrysogenum, supporting the protective role of alternative respiration against oxidative damage in cells.…”
Section: The Role Of Aox In Oxidative Stressmentioning
confidence: 99%
“…While animals posses only cytochrome respiratory pathway (cyanide-sensitive respiration, CSR), performed by the single terminal CytC oxidase (COX), most fungi, apart of classical cytochrome respiratory pathway, just like plants, also posses alternative respiration (cyanide-resistant respiration, CRR) sensitive to SHAM, and performed by alternative oxidase (AOX) which is located in the inner mitochondrial membrane (JosephHorne et al 2001). Unlike plants, where CRR is found in all species investigated to date, it is absent in fungi capable of aerobic fermentation (Veiga et al 2000). In the rest of fungi the AOX expression and activity are very complex and highly diverse among different species.…”
Section: Introductionmentioning
confidence: 99%
“…While the increasing body of evidence shows that AOX in plants plays a role in lowering mitochondrial reactive oxygen species (ROS) formation (Maxwell et al 1999;Yip and Vanlerberghe 2001), in fungi this function could not be confirmed (Veiga et al 2003a). Even more, in Podospora anserina mutant overexpression of AOX considerably increased ROS production (Lorin et al 2001).…”
Section: Introductionmentioning
confidence: 99%